The Minimal Clinically Important Difference for Achievement of Substantial Reperfusion With Endovascular Thrombectomy Devices in Acute Ischemic Stroke Treatment - Lin, Chun-Jen; Saver, Jeffrey L. (Frontiers in Neurology, 2020)
Background and Purpose: Recent non-inferiority clinical trials of novel endovascular thrombectomy devices for acute ischemic stroke have used the primary outcome of achievement of substantial reperfusion. Determining the minimal clinically important difference (MCID) is an essential step for the design of non-inferiority clinical trials. Methods: We surveyed international neuro-interventionalist and non-interventional vascular neurologist investigators. The questionnaire included demographic characteristics, level of clinical experience, and their MCID clinical scenario-based judgment regarding the MCID for the outcome substantial reperfusion (Thrombolysis in Cerebral Infarction score 2b-3) within 3 passes. Results: Survey responses were received from 58 of 200 experts. Among responders, 75.9% were neuro-interventionalists (most commonly interventional neuroradiologists and interventional neurologists, followed by endovascular neurosurgeons) and 24.1% non-interventional vascular neurologists. 87.9% had been in practice for more than 5 years and 67.3% devoted more than half of their practice to stroke care. Responder-non-responder and continuum of resistance analysis indicated responders were representative of the full expert population. Among experts, the median MCID for substantial reperfusion was 3.1-5% (IQR 1.1-3% to 5.1-10%). MCID distributions did not differ among neuro-interventionalists and non-interventional vascular neurologists. Conclusions: Neuro-interventionl and non-interventional stroke experts judged that the minimal clinically important difference in comparing thrombectomy devices for achieving substantial reperfusion is 3.1-5%. This MCID, lower than non-inferiority margins used in several recent clinical trials, can inform trial designs and clinical development.